2012
DOI: 10.4049/jimmunol.1202317
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Long-Lived Plasma Cells and Their Survival Niches in Autoimmunity, Malignancy, and Allergy

Abstract: Long-lived plasma cells survive in a protected microenvironment for years or even a lifetime and provide humoral memory by establishing persistent Ab titers. Long-lived autoreactive, malignant, and allergen-specific plasma cells are likewise protected in their survival niche and are refractory to immunosuppression, B cell depletion, and irradiation. Their elimination remains an essential therapeutic challenge. Recent data indicate that long-lived plasma cells reside in a multicomponent plasma cell niche with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 79 publications
1
72
0
Order By: Relevance
“…Furthermore, comparative studies of the phenotype, BLIMP1 expression, gene expression profiling, and IGVH gene somatic hypermutation support the view that human PCs obtained from tonsil (To) and lymph node (as examples of early PCs from inductive SLOs), from the peripheral blood (PB) drawn at the peak time of appearance of Ag-induced PCs (as a source of transitional PCs), and from the BM (as terminally differentiated PCs) exhibit a gradient of increasing maturation in the following direction: SLOs→blood→BM (16)(17)(18)(19)(20). Besides this well-established migratory pathway, evidence in both humans and mice indicates that a non-negligible fraction of PCs survives in the SLOs, as well as in inflamed tissues, where they continue to produce Abs for prolonged periods (21)(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comparative studies of the phenotype, BLIMP1 expression, gene expression profiling, and IGVH gene somatic hypermutation support the view that human PCs obtained from tonsil (To) and lymph node (as examples of early PCs from inductive SLOs), from the peripheral blood (PB) drawn at the peak time of appearance of Ag-induced PCs (as a source of transitional PCs), and from the BM (as terminally differentiated PCs) exhibit a gradient of increasing maturation in the following direction: SLOs→blood→BM (16)(17)(18)(19)(20). Besides this well-established migratory pathway, evidence in both humans and mice indicates that a non-negligible fraction of PCs survives in the SLOs, as well as in inflamed tissues, where they continue to produce Abs for prolonged periods (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…These latter are generated in tissue niches, which provide the PCs with appropriate survival factors. The different auxiliary cell types, and the cytokines and other molecules reported as participants in PC survival niches have been recently revised (24,31). In a previous study, we have demonstrated that human SLO, but not BM, PCs express IL-21R and respond to IL-21 by activating STAT-3 and increasing their survival (32).…”
mentioning
confidence: 99%
“…We therefore conclude that our Siglec-G B6 2/2 mice were sufficiently backcrossed to B6 to exclude unspecific genetic background effects of the remaining 5.4% BALB/c genome. A hallmark of many autoimmune diseases is the occurrence of pathogenic autoantibodies produced by self-reactive plasma cells (39,40). In Siglec-G B6 2/2 and Siglec-G B6 2/2 3 FcgRIIb B6…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies evidenced 2 IgG oligoclonal bands (OCB) with 3 IgG4 OCB in the CSF of Patient 1 ( Figure 1B) and a single IgG OCB with 2 IgG4 OCB in the CSF of Patient 2; no corresponding bands were detected in the patients' sera. OCB are the expression of a CNS and CSF compartmentalization of a highly restricted number of antigen specific B-cell clones that were transformed, after affinity maturation, into Ig-secreting plasma cells 8,9 . Therefore, our results demonstrate that oligoclonally restricted IgG4-positive plasma cells residing in meningeal inflammatory niches are involved in the pathogenesis of IgG4-HP and support a pathogenetic model in which a fibroinflammatory immune reaction is initially triggered by a specific response against a still unknown antigen.…”
Section: Rheumatologymentioning
confidence: 99%